Combination lashgan Aggregatlarda Zanzhirli Uzatmaning Ishlash Muddatini Aniglash - Raxmonov Xusan Tojievich; Xusanov Axmadjon Jo'raevich (Peerian Journals Publishing, 2022)
The article describes the movement of the chain through the tension roller in the chain drive in the combined unit is sufficiently regulated, reducing the load on each tooth andchain hinge due to the increase in the angles of sprocket coverage
Keywords: Chain drive; speed; power